Ecological intensification and arbuscular mycorrhizas: a meta-analysis of tillage and cover crop effects - Bowles, Timothy M.; Jackson, Louise E.; Loeher, Malina; Cavagnaro, Timothy R. (The Journal of applied ecology, 2017)
1. Reliance on ecosystem services instead of synthetic, non-renewable inputs is increasingly seen as key to achieving food security in an environmentally sustainable way. This process, known as ecological intensification, will depend in large part on enhancing below-ground biological interactions that facilitate resource use efficiency. Arbuscular mycorrhizas (AM), associations formed between the roots of most terrestrial plant species and a specialized group of soil fungi, provide valuable ecosystem services, but the full magnitude of these services may not be fully realized under conventional intensively managed annual agricultural systems. 2. Here, we use meta-analysis to assess how reducing soil disturbance and periods without roots in agricultural systems affect the formation of AM and the diversity and community composition of arbuscular mycorrhizal fungi (AMF). We compiled data from 54 field studies across five continents that measured effects of tillage and/or cover cropping on AMF colonization and/or communities and assessed effects of management and environmental factors on these responses. 3. Less intensive tillage and winter cover cropping similarly increased AMF colonization of summer annual cash crop roots by ~30%. The key variables influencing the change in AMF colonization were the type of cover crop or the type of alternative tillage, suggesting that farmers can optimize combinations of tillage and cover crops that most enhance AM formation, particularly with no-till systems and legume cover crops. 4. Richness of AMF taxa increased by 11% in low-intensity vs. conventional tillage regimes. Several studies showed changes in diversity and community composition of AMF with cover cropping, but these responses were not consistent. 5. Synthesis and applications. This meta-analysis indicates that less intensive tillage and cover cropping are both viable strategies for enhancing root colonization from indigenous arbuscular mycorrhizal fungi (AMF) across a wide range of soil types and cash crop species, and possibly also shifting AMF community structure, which could in turn increase biologically based resource use in agricultural systems.